2013
DOI: 10.1016/j.jhep.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient particulate matter induces a NASH-like phenotype and impairs hepatic glucose metabolism in an animal model

Abstract: Background Air pollution is a global challenge to public health. Epidemiological studies have linked exposure to ambient particulate matter with aerodynamic diameters < 2.5 μm (PM2.5) to the development of metabolic diseases. In this study, we investigated the effect of PM2.5 exposure on liver pathogenesis and the mechanism by which ambient PM2.5 modulates hepatic pathways and glucose homeostasis. Methods Using “Ohio’s Air Pollution Exposure System for the Interrogation of Systemic Effects (OASIS)-1”, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
190
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 273 publications
(212 citation statements)
references
References 33 publications
15
190
1
6
Order By: Relevance
“…While concern over environmental issues in countries such as China and India have mounted in the last few years, the awareness or knowledge that pervasive environmental toxins may pose a risk for chronic cardiovascular and CM diseases is rather limited. Our previous studies, along with others, have provided credible initial evidence in experimental animal models that inhaled particulates such as air-pollution may indeed interact with other risk factors in predisposing to T2DM via a variety of mechanisms including potentiation of inflammation, promotion of endoplasmic reticulum (ER) stress, alteration in brown adipose tissue function and change in autonomic tone 5, 12, 1417, 2529 . However, there is still inadequate prospective information from urban environments exposed to high levels of air-pollution over chronic durations that will allow discernment of potential threshold concentrations for health responses and interaction with other common factors such as diet, activity and exercise.…”
Section: Discussionmentioning
confidence: 82%
“…While concern over environmental issues in countries such as China and India have mounted in the last few years, the awareness or knowledge that pervasive environmental toxins may pose a risk for chronic cardiovascular and CM diseases is rather limited. Our previous studies, along with others, have provided credible initial evidence in experimental animal models that inhaled particulates such as air-pollution may indeed interact with other risk factors in predisposing to T2DM via a variety of mechanisms including potentiation of inflammation, promotion of endoplasmic reticulum (ER) stress, alteration in brown adipose tissue function and change in autonomic tone 5, 12, 1417, 2529 . However, there is still inadequate prospective information from urban environments exposed to high levels of air-pollution over chronic durations that will allow discernment of potential threshold concentrations for health responses and interaction with other common factors such as diet, activity and exercise.…”
Section: Discussionmentioning
confidence: 82%
“…O 3 exposure also changed the expression of several genes involved in inflammatory processes that tended to be inhibited rather than induced. Air pollution has been recently linked to non-alcoholic liver disease, also known as liver steatohepatitis (Zheng et al, 2013; Lin et al, 2014). One experimental study involving long-term exposure to concentrated ambient PM has shown liver inflammation, fibrosis and changes in markers of insulin signaling (Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution has been recently linked to non-alcoholic liver disease, also known as liver steatohepatitis (Zheng et al, 2013; Lin et al, 2014). One experimental study involving long-term exposure to concentrated ambient PM has shown liver inflammation, fibrosis and changes in markers of insulin signaling (Zheng et al, 2013). Marked acute effects of O 3 on liver gene expression reflecting apoptosis, alteration of mitochondrial function and metabolic processes in the present study support the hypothesis that air pollutants could, over a long period of time, induce liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serine phosphorylation of IRS-1 is indeed triggered by many diabetogenic factors, especially through the stress signaling pathways that have been shown to contribute to the development of IR (51). PM 2.5 exposure activates JNK and downregulates the IRS1-mediated signaling in the liver, leading to glucose intolerance and IR (52). In addition, specific overexpression of a constitutively active JNK in skeletal muscle has been shown to be sufficient to induce whole-body IR through impairment of insulin signaling (53).…”
Section: O 3 Induces Production Of Toxic Lung Mediatorsmentioning
confidence: 99%